2018
DOI: 10.1021/acsami.8b03185
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Graphene-Based Nanocomposite (GO–PEI–Ag) with Broad-Spectrum, Long-Term Antimicrobial Activity and Antibiofilm Effects

Abstract: Various silver nanoparticle (AgNP)-decorated graphene oxide (GO) nanocomposites (GO-Ag) have received increasing attention owing to their antimicrobial activity and biocompatibility; however, their aggregation in physiological solutions and the generally complex synthesis methods warrant improvement. This study aimed to synthesize a polyethyleneimine (PEI)-modified and AgNP-decorated GO nanocomposite (GO-PEI-Ag) through a facile approach through microwave irradiation without any extra reductants and surfactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(88 citation statements)
references
References 52 publications
2
86
0
Order By: Relevance
“…Analogously, the destabilization of the cell outer membrane in gram-negative bacteria was observed through the accumulation of envelope protein precursors after exposure to AgNPs and GO-AgNPs, even in gram-positive bacteria with a strong physical barrier (Chen et al, 2014;Zhao et al, 2018). Previous results, reported by Leung and coworkers, proved that nMgO directly interacted with Escherichia coli and caused the downregulation of outer membrane proteins (Omp), such as channel porins and ion channel proteins, as well as disturbance of proteins involved in the membrane lipid metabolism process, making cells liable to lyse (Leung et al, 2014).…”
Section: Destabilization Of Fungal Cell Membranementioning
confidence: 98%
See 1 more Smart Citation
“…Analogously, the destabilization of the cell outer membrane in gram-negative bacteria was observed through the accumulation of envelope protein precursors after exposure to AgNPs and GO-AgNPs, even in gram-positive bacteria with a strong physical barrier (Chen et al, 2014;Zhao et al, 2018). Previous results, reported by Leung and coworkers, proved that nMgO directly interacted with Escherichia coli and caused the downregulation of outer membrane proteins (Omp), such as channel porins and ion channel proteins, as well as disturbance of proteins involved in the membrane lipid metabolism process, making cells liable to lyse (Leung et al, 2014).…”
Section: Destabilization Of Fungal Cell Membranementioning
confidence: 98%
“…Several studies have suggested that the formation of reactive oxygen species (ROS) and its accumulation in cells seem to be the underlying mechanism of metal nanoparticles against bacterial pathogens, particularly because the generated ROS directly destroy the cell multiplication capacity (Horst et al, 2013;Chen et al, 2014). It is generally believed that microorganism disinfection relies on the direct interaction between nanoparticles and biological cells (Chen et al, 2012;Zhao et al, 2018). In particular, Huang et al, further demonstrated that peptide linkages in the bacterial cell wall are physically damaged by the generation of superoxide ions on the surface of nMgO (Huang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to studies investigating the biological impact of GFNs on microbial systems, many publications have reported the antibacterial properties of different graphene derivatives and composites [9][10][11][12][13] . In case of the interactions between fungi and graphene-based materials, most of the efforts have focused on improving the antifungal properties of GFNs through their modification with antimycotic drugs, peptides or metals [14][15][16][17] .…”
mentioning
confidence: 99%
“…6 and 16) to 48 h. 30 Studies of "prolonged exposure" reported either antibacterial activity aer long term storage of the nanomaterials repeated exposures 31,32 and the exposure of bacteria to such nanomaterials for durations longer than 24 h with subsequent monitoring of bacterial growth are relatively uncommon. 31,33 Our understanding of the underlying mechanism of the existing long term antibacterial activity of nanoparticles in vitro/ vivo is still relatively nascent. 34 The simultaneous existence of ROS and non ROS mediated long term antibacterial activity in nanomaterials is therefore an important area of research.…”
Section: Introductionmentioning
confidence: 99%